PARASITISASI DAN KAPASITAS REPRODUKSI COTESIA FLAVIPES CAMERON (HYMENOPTERA: BRACONIDAE) PADA INANG DAN INSTAR YANG BERBEDA DI LABORATORIUM - Purnomo . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2006)
Parasitization and reproductive capacity of Cotesia flavipes Cameron (Hymenoptaera: Braconidae) on different hosts and instar in laboratory. C. flavipes is an important parasitoid on sugar cane spotted borer, Chilo sacchariphagus Bojer. The biology informations of C. flavipes is needed in order to make more effective as acontroling agent. The objectives of this research were to investigate the effect of host species (C. sacchariphagus, C. auricilius, Scirpophaga nivella) and different instar on parasitization and reproductive capacity of C. flavipes. The results showed that the best host for C. flavipes is C. sacchariphagus and at fifth instar of C. sacchariphagus.